LD-aminopterin in the canine homologue of human atopic dermatitis: a randomized, controlled trial reveals dosing factors affecting optimal therapy. - John A Zebala; Alan Mundell; Linda Messinger; Craig E Griffin; Aaron D Schuler; Stuart J Kahn (PLoS ONE)
Background Options are limited for patients with atopic dermatitis (AD) who do not respond to topical treatments. Antifolate therapy with systemic methotrexate improves the disease, but is associated with adverse effects. The investigational antifolate LD-aminopterin may offer improved safety. It is not known how antifolate dose and dosing frequency affect efficacy in AD, but a primary mechanism is thought to involve the antifolate-mediated accumulation of 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR). However, recent in vitro studies indicate that AICAR increases then decreases as a function of antifolate concentration. To address this issue and understand how dosing affects antifolate efficacy in AD, we examined the efficacy and safety of different oral doses and schedules of LD-aminopterin in the canine model of AD. Methods and findings This was a multi-center, double-blind trial involving 75 subjects with canine AD randomized to receive up to 12 weeks of placebo, once-weekly (0.007, 0.014, 0.021 mg/kg) or twice-weekly (0.007 mg/kg) LD-aminopterin. The primary efficacy outcome was the Global Score (GS), a composite of validated measures of disease severity and itch. GS improved in all once-weekly cohorts, with 0.014 mg/kg being optimal and significant (43%, P<0.01). The majority of improvement was seen by 8 weeks. In contrast, GS in the twice-weekly cohort was similar to placebo and worse than all once-weekly cohorts. Adverse events were similar across all treated cohorts and placebo. Conclusions Once-weekly LD-aminopterin was safe and efficacious in canine AD. Twice-weekly dosing negated efficacy despite having the same daily and weekly dose as effective once-weekly regimens. Optimal dosing in this homologue of human AD correlated with the concentration-selective accumulation of AICAR in vitro, consistent with AICAR mediating LD-aminopterin efficacy in AD.